2019
DOI: 10.1074/jbc.ra118.006846
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific glycation of Aβ1–42 affects fibril formation and is neurotoxic

Abstract: A␤1-42 is involved in Alzheimer's disease (AD) pathogenesis and is prone to glycation, an irreversible process where proteins accumulate advanced glycated end products (AGEs). N ⑀-(Carboxyethyl)lysine (CEL) is a common AGE associated with AD patients and occurs at either Lys-16 or Lys-28 of A␤1-42. Methyglyoxal is commonly used for the unspecific glycation of A␤1-42, which results in a complex mixture of AGE-modified peptides and makes interpretation of a causative AGE at a specific amino acid residue difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Another, frequently used, method to obtain monomeric Aβ solutions is pre-treatment with alkaline reagents such as NH 4 OH or NaOH, which prevents the Aβ solution of reaching the isoelectric point of 5.5 at which Aβ aggregation is maximal [78][79][80]. We followed a previously established protocol based on this latter method [30,[81][82][83][84][85] for the preparation of aggregate-free Aβ solutions and found that it tremendously increased reproducibility of our findings as compared with HFIP pre-treatment. Furthermore, we carefully controlled experimental conditions by determination and normalization of Aβ concentrations before every experiment, as we observed a high variation in actual protein content of commercially available Aβ peptides, often not consistent with the indicated amounts.…”
Section: Discussionmentioning
confidence: 87%
“…Another, frequently used, method to obtain monomeric Aβ solutions is pre-treatment with alkaline reagents such as NH 4 OH or NaOH, which prevents the Aβ solution of reaching the isoelectric point of 5.5 at which Aβ aggregation is maximal [78][79][80]. We followed a previously established protocol based on this latter method [30,[81][82][83][84][85] for the preparation of aggregate-free Aβ solutions and found that it tremendously increased reproducibility of our findings as compared with HFIP pre-treatment. Furthermore, we carefully controlled experimental conditions by determination and normalization of Aβ concentrations before every experiment, as we observed a high variation in actual protein content of commercially available Aβ peptides, often not consistent with the indicated amounts.…”
Section: Discussionmentioning
confidence: 87%
“…To further clarify the pathological significance of glycated Aβ 42 , a recent study examined the characteristics of three glycated Aβ 42 variants compared to non-glycated Aβ 42 . The glycated variants possessed site-specific glycation at Lys16, Lys28, or Lys16 and Lys28 [84]. Transmission microscopy and in silico modeling revealed that double Aβ 42 glycation at Lys16 and Lys28 reduced free energy change and destabilized fibril structures, thereby increasing the rate of Aβ 42 aggregation [84].…”
Section: Potential Mechanisms Underlying Increased Cytotoxicity Of Glmentioning
confidence: 99%
“…The glycated variants possessed site-specific glycation at Lys16, Lys28, or Lys16 and Lys28 [84]. Transmission microscopy and in silico modeling revealed that double Aβ 42 glycation at Lys16 and Lys28 reduced free energy change and destabilized fibril structures, thereby increasing the rate of Aβ 42 aggregation [84]. They also showed that a single glycation at Lys16 slowed down fibril formation, whereas a single glycation at Lys28 had no significant effect [84].…”
Section: Potential Mechanisms Underlying Increased Cytotoxicity Of Glmentioning
confidence: 99%
See 2 more Smart Citations